Innovation and VET student work placement. (2nd October 2019) - Hodge, Steven; Smith, Ray
ABSTRACT: Although vocational education and training (VET) is often sidelined in policy debates about innovation and how to promote it, some research and theory highlights ways the sector does contribute. VET can be, for example, positioned as an instrument of 'knowledge diffusion' and thereby an active element in so-called 'innovation systems'. But the role of work placement students in the overall contribution of VET to innovation has not been directly considered. This paper presents research into the possibility that VET placement students may indeed play such a role. This qualitative project involving an exploratory phase and four case studies indicates that placement students can, in some circumstances, play a discernible role in knowledge diffusion. The research also suggests that there are cases where students can play a direct role in small-scale innovation in the practice of organisations. At the same time, the research suggests employers, training provider staff and students themselves are influenced by stereotypes that may make it difficult to anticipate and acknowledge such innovation. With some work on stakeholder attitudes, it may be possible to tap into a hidden source of innovation.